Acute lymphoblastic leukemia in a child presenting primarily with priapism - Garima Gupta; Deepak Kumar; Maharishi Trivedi (Wolters Kluwer Medknow Publications, 2020)
Priapism is an uncommon presentation in children and adults with a chronic myeloid type of leukemia. Its association is rarely found in an acute lymphoblastic type of leukemia (ALL). Timely management is important to prevent irreversible complications. We report a case of ALL with presenting complaint of priapism.